(untitled) (Physical Education, Health and Social Sciences, 2026)
Drug trafficking has become a serious national security threat in Pakistan Moreover, it has become a complicated issue which possesses strategic ramifications; including national stability, regional security and international standing. Pakistan’s geographic position in the region, the fact that Afghanistan has become the world’s leading producer of illicit opiates, the porous border in the west, the long coastal stretch on the Arabian Sea, and the emerging trade and transit infrastructures has put Pakistan on important international drug smuggling routes. (UNODC, UNODC World Drug Report 2025, 2025). South-West Asia is a key location for heroin trafficking in the world. New developments include the arrival of synthetic drugs, like methamphetamine, as much as this region is an opiate-dominant area. According to the seizure statistics between 2019 and 2023, there is a steady trend in heroin seizures while methamphetamine seizures are on the rise in the region. The study derives its analytical framework developed by drawing on the UNODC World Drug Report datasets, Anti-Narcotics Force seizure statistics and literature on transnational organized crimes. The route-based framework associates geography with trafficking by institutions responsible for such. The research identifies that Pakistan is involved in four major trafficking domains: (1) Land routes in the west which passes through Afghanistan; (2) Internal routes which passes through the country from the border to the logistics areas; (3) Maritime trafficking which passes through the Makran coast and Arabian Sea; and (4) Air routes which are used for transporting synthetic drugs. The findings are Narcotics trafficking undermines internal stability, creates economic security challenges, and damages international reputation. The financial flows generated by drug trade fuel organized crime, corruption, and possible support for violent non-state actors. The linkages between narcotics trafficking networks and trade systems, as well as maritime trade networks, reveal vulnerabilities in Pakistan’s trade systems, maritime trade networks, and financial systems. The interdiction capabilities of Pakistan, as led by Anti-Narcotics Force (ANF) and assisted by Pakistan Customs, Pakistan Coast Guards, Maritime Security Agency, and Provincial law enforcement agencies, have shown improvement. However, narcotics trafficking networks are robust, adaptive, and increasingly integrated into trade systems, maritime networks, and trade logistics. (Ministry Of Narcotics Control, 2024) ((WCO), 2024) The research concludes that drug trafficking through Pakistan needs to be addressed as a strategic national security concern rather than an enforcement challenge. A comprehensive national strategy is required to counter drug trafficking.